Why did I say sorry? Apology motives and transgressor perceptions of reconciliation. (23rd June 2019) - Mu, Frank; Bobocel, D. Ramona
Summary: Despite the importance of apology in reconciling interpersonal transgressions, little research has focused on the people engaging in the behavior. Why do transgressors apologize in the workplace, and do apology motives shape transgressor perceptions of reconciliation? We conducted three field studies using qualitative and quantitative methodologies to examine these questions. In Studies 1 and 2 (total N = 781), we identified four distinct apology motives—self‐blame, relational value, personal expedience, and fear of sanctions—and developed self‐report scales to measure the motives. In Study 3 ( N = 420), we examined relations between apology motives and transgressor perceptions of victim forgiveness and relationship reconciliation through the lens of motivated cognition. We found that apologizing due to self‐blame, relational value, and personal expedience increases perceptions of victim forgiveness, whereas apologizing due to fear of sanctions decreases perceived forgiveness. Moreover, mediation analyses revealed that motives indirectly influence transgressor perceptions of relationship reconciliation through perceived forgiveness. Taken together, our research presents a novel multidimensional perspective on apology‐giving in the workplace, suggesting that why transgressors apologize can affect their perceptions of reconciliation. Overall, our research highlights the need to incorporate transgressor cognitive and motivational processes into reconciliation research.